Impressed with ChatGPT's agricultural knowledge? CGIAR's open access effort (probably)* enabled it - Koo, Jawoo; Devare, Medha; King, Brian (CGIAR System Organization, 2023)
2023 will be remembered as the year when the communication barrier between human and machine intelligence was breached, as online chatbots such as ChatGPT went public able to respond intelligibly to questions and even perform language-based tasks. It is possible that in the near future we could see these large-scale machine learning models having an impact in agri-food systems, for example by providing individually tailored advice to smallholder farmers.